The Influence of Anemia History in Pregnant Mothers Towards the Growth and Development of Infants - Juana Linda Simbolon; Emilia Silvana Sitompul (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Anemia in pregnancy still becomes a significant problem globally, impacting the mother and the fetus she contains. The effects of anemia on the fetus include low birth weight, lack of oxygen in the womb, and spontaneous and regular breathing failure. These disorders can hinder the growth and development of the baby become not optimal. Early detection is important to determine if there are growth and development disorders in a later period so that appropriate treatment can be carried out immediately and adverse effects can be minimized. This type of research is quantitative analytic, and the study design used is a cross-sectional study. The population in this study were mothers with a history of pregnancy with anemia and infants 0-3 months. Obtained a sample of 112 people. Data analysis using univariate analysis, bivariate with Chi-square with a 95% confidence level, and multivariate using multiple logistic regression test. The results of this study show there is an influence of age, education, parity, nutrition history of anemia in pregnant women with growth and development of infants aged 0-3 months. The nutritional variable is 3,643 times more significant in influencing the baby's growth and development. Mother is expected to provides exclusive breastfeeding for infats aged from 0-6 months. The application of the Primaku soft application developed by IDAI is a breakthrough in the world of child health that can help parents understand the health conditions of their children online. Abstrack: Anemia pada kehamilan masih merupakan masalah utama di dunia yang memiliki dampak pada ibu dan janin yang dikandungnya. Dampak anemia pada janin diantaranya berat badan lahir rendah, kekurangan oksigen dalam kandungan serta kegagalan nafas spontan dan teratur. Gangguan tersebut dapat menyebabkan pertumbuhan dan perkembangan bayi tidak optimal. Deteksi dini merupakan hal yang penting untuk mengetahui adanya gangguan tumbuh kembang pada periode lebih lanjut sehingga penanganan yang tepat dapat segera dilakukan dan efek buruk dapat diminimalkan. Penelitian ini menggunakan metode kuantitatif analitik dengan desain yang digunakan adalah Cross-sectional Study. Populasi dalam penelitian ini adalah ibu dengan riwayat hamil dengan anemia dan bayi 0-3 bulan. Didapatkan sampel berjumlah 112 orang. Analisa data menggunakan analisis univariat, bivariat dengan Chi-square dengan derajat kepercayaan 95 %, dan multivariat dengan menggunakan uji regresi logistik berganda. Hasil penelitian ini menunjukkan ada pengaruh umur, pendidikan, paritas, nutrisi riwayat anemia ibu hamil dengan tumbuh kembang bayi usia 0-3 bulan.Variabel nutrisi 3,643 kali lebih besar berpengaruh terhadap tumbuh kembang bayi. Ibu diharapkan memberikan ASI Eksklusif 0-6 bulan. Penerapan soft aplikasi Primaku yang dikembangkan oleh IDAI merupakan sebuah terobosan di dunia kesehatan anak dapat membantu para orang tua memahami kondisi kesehatan buah hatinya secara online.